Results of Endovascular Treatment for High-Flow Direct Carotid-Cavernous Fistulas - A. E. Petrov; S. А. Goroshchenko; L. V. Rozhchenko; K. A. Samochernykh (Вестник рентгенологии и радиологии, 2020)
Objective: to study the results of treatment in patients with direct high-flow carotid-cavernous fistulas with their transarterial occlusion using detachable balloons and microcoils.Material and methods. Thirty-five patients underwent surgery using detachable balloons and microcoils. The clinical picture in all patients was represented by pulsating exophthalmos, ptosis on the side of the lesion, ophthalmoplegia, and conjunctival chemosis.Results. In all patients closure of carotid-cavernous fistulas and reversal of symptoms were achieved after primary surgery. Internal carotid artery reconstruction with microcoils could be achieved significantly more often than that with balloons. An anastomotic recurrence was significantly more common in patients undergoing surgery with balloons.Conclusion. The use of microcoils allows to perform reconstructive surgery significantly more frequently, while the recurrence rate is significantly lower than after using the balloons.